Describing the characteristics, treatment pathways and outcomes of people with chronic low back pain managed by a pain management Service in Nottingham and generating indicative estimates of cost-effectiveness - Almazrou, Saja (2018)
Background: Chronic low back pain (CLBP) is a highly prevalent condition that has substantial impact on patients, the healthcare system and society. Its aetiology is complex and the condition can be exacerbated by many psychological, physical and social factors. Pain management services (PMS), which aim to address the complex nature of back pain, are recommended in clinical practice guidelines to manage CLBP. Although the effectiveness of such services has been widely investigated in relation to CLBP, the quality of evidence underpinning the use of these services remains moderate. Given that these services are resource intensive, evidence is needed to determine their cost-effectiveness. Aim: This study aims to describe the patient characteristics, clinical outcomes and healthcare resource use of people with CLBP in a community-based pain management service (PMS) in Nottingham to derive an indicative estimate of the cost effectiveness of PMS compared with standard care (SC). Methods: The study followed the Medical Research Council (MRC) guidance for evaluating complex interventions. The MRC suggest conducting developmental and observational work before evaluating complex interventions on a larger scale. Therefore, this PhD research includes a service evaluation study, which was conducted in two community-based PMS in Nottingham. This was followed by a systematic review of the cost effectiveness of a PMS in CLBP. Finally, a decision analysis model was developed to assess the cost effectiveness of PMS compared with SC. In the service evaluation study, newly referred people with CLBP who provided written consent were included. Participants provided information on health status and healthcare resource use using postal questionnaires and diaries at baseline and then three and six months after recruitment. The outcome measures were the Brief Pain Inventory (BPI), the Roland Morris Disability Questionnaire (RMDQ) and the EuroQoL (EQ-5D-3L). In the systematic review, electronic searches were conducted in clinical and economic databases from their inception to August 2017. Full economic evaluations, undertaken from any perspective, conducted alongside randomised clinical trials (RCTs) or based on decision analysis models were included. The Cochrane Back Review Group (CBRG) risk assessment and the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist were used to assess the methodological quality of eligible studies. These studies informed the development of an economic evaluation based on a decision analysis model to compare PMS with SC. Costs per extra quality-adjusted-life-year (QALY) were calculated from the UK National Health Service (NHS) England perspective using a lifetime horizon. Transition probability, utilities, healthcare resource use and costs were obtained from the service evaluation study and the published literature. Results: In the service evaluation study, 32 people were recruited over 10 months. The mean age was 58.8 years with an equal distribution of both genders. The dropout rates were 21% and 25% over three and six months respectively.